1996
DOI: 10.1016/s0022-5347(01)66504-2
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Penile Appearance after Hypospadias Surgery: The Patient and Surgeon View

Abstract: Purpose: We studied the degree of agreement between hypospadias patient and surgeon satisfaction with the cosmetic surgical result, and the relation between penile length, m e a d position and patient satisfaction.Materials and Methods: Cosmetic and functional results in 35 boys with hypospadias were assessed, and a standardized questionnaire was completed by patients and surgeon.Results: There was hardly any agreement between patient and surgeon satisfaction with patient penile appearance. Patients were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(82 citation statements)
references
References 16 publications
3
78
1
Order By: Relevance
“…In a study of 100 patients with proximal hypospadias and severe curvature, recurrent curvature was reported in a total of 22 patients, including three (of 32) children who underwent ventral lengthening procedures and 19 (of 68) who underwent dorsal plication (9% versus 28%; P = 0.03). 6 This study suggests that ventral lengthening could be more effective and durable in achieving penile straightening. However, in another study of 22 patients with recurrent curvature >10 years after initial penile straightening, 19 patients had received dorsal plication as their initial procedure and three had undergone ventral tunica vaginalis grafting.…”
Section: Focus On Paediatric Urologymentioning
confidence: 73%
See 2 more Smart Citations
“…In a study of 100 patients with proximal hypospadias and severe curvature, recurrent curvature was reported in a total of 22 patients, including three (of 32) children who underwent ventral lengthening procedures and 19 (of 68) who underwent dorsal plication (9% versus 28%; P = 0.03). 6 This study suggests that ventral lengthening could be more effective and durable in achieving penile straightening. However, in another study of 22 patients with recurrent curvature >10 years after initial penile straightening, 19 patients had received dorsal plication as their initial procedure and three had undergone ventral tunica vaginalis grafting.…”
Section: Focus On Paediatric Urologymentioning
confidence: 73%
“…The surgeon often has to rely on patient or parental report, which can vary significantly from surgeon assessment. 6 If physical examination during erection is unrealistic, photographs should be taken by the patient during erection. In any case, if the correction of residual or recurrent curvature is elected, an intraoperative erection test is mandatory before embarking on any further procedure.…”
Section: Focus On Paediatric Urologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, with regard to the parents and the urologist's evaluation, it seems to be unlikely that this is the sole reason and other causes must be considered. Mureau has published an extensive survey on patient's satisfaction after hypospadias repair with a similar study design and found that his patients were less satisfied with the penile appearance than the treating surgeons 5 . In that questionnaire, 3 out of 8 items were related to penile size and one to the appearance of the scrotum and testes, so that comparison to our results is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies have shown that the absence of the prepuce is one of the features that remind patients of the surgery they underwent as children [28]. Örtqvist et al [29] have reported that one-third of Swedish adults who had undergone HR in combination with circumcision in childhood declared they wished they had the foreskin intact.…”
Section: Relevance Of Pr For Parents and Patientsmentioning
confidence: 99%